Hambatan Pengimplementasian Laporan Keuangan Usaha Mikro Kecil dan Menengah (UMKM) Berbasis Digital - Rahmatia Rahmatia; Muhammad Ardi; Afriana Lomagio; Ririn Paputungan; Novia A Mustava (Al-Buhuts, 2024)
This research aims to analysed the barriers in implementing the preparation of financial reports based digital for UMKM in Gorontalo. This reseach was a type of quantitative reseach with a Participatory Action Research (PAR) approach which consists of four stages, namely (1) Identifying the Research Question. (2) Gathering the information to answer the question, (3) Analyzing and interpreting the information, dan (4) Sharing the results with the participant. The research results show that there are several factors what can barriers the implementation of a financial reporting system UMKM based digital, namely the lack of business actors’ knowledge regarding the preparation of financial reports and technology, as well as the low interest of UMKM. This research highlights the barriers in implementing financial reports based digital for UMKM. These barriers then become a reference in designing a digital system for UMKM SIAM Syariah financial reports adapted to the needs and conditions of business actors. This information system based digital expected to produce relevant and reliable information according to the needs of UMKM. Different from previous research, this research did not just focus on the barriers to implementing financial reports in UMKM, but also provides concrete and practicial solutions to support of the implementation reports based digital in UMKM.